Effects of exercise cessation on adipose tissue physiological markers related to fat regain: A systematic review - Fabrício Boscolo Del Vecchio; Victor Silveira Coswig; Leo Dutra Cabistany; Rafael Bueno Orcy; Paulo Gentil (SAGE Open Medicine, 2020)
Tissues usually super compensate during the period that follow physical exercise. Although this is widely accepted for muscle and glycogen, the compensatory effect is not usually applied to fat tissues. Notwithstanding, evidence for this has been present since the 1970s when it was first suggested that the increased lipogenic activity in response to training might be an adaptation that enables to restore an energy reserve that can be used in times of need. In this context, the present review aimed to summarize information about the effect of detraining on fat metabolism and the physiological responses associated with fat regain. A systematic search on PubMed and Scielo was performed using “training cessation,” “detraining,” “exercise detraining,” and “exercise cessation” combined with “fat tissue,” “adipose tissue,” “adipose metabolism,” and “fat metabolism,” as descriptors. From 377 results, 25 were included in this review, 12 humans and 13 rodents, resulting in a sample of 6772 humans and 613 animals. The analysis provided evidence for fat super compensation, as well as differences in humans and rodents, among different protocols and possible mechanisms for fat gain after exercise cessation. In summary, exercise cessation appears to increase the ability of the adipose tissue to store energy. However, caution should be taken, especially regarding conclusions based on investigations on humans, considering the multiple factors that could affect fat metabolism.